2021
DOI: 10.1002/pan3.10176
|View full text |Cite
|
Sign up to set email alerts
|

Urban versus rural? The effects of residential status on species identification skills and connection to nature

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 80 publications
0
26
0
1
Order By: Relevance
“…This has led some to argue that people's levels of direct experiences of nature may not have actually decreased [67,68]. Fourth, our study measured teachers' levels of ecological knowledge using only their ability to identify species of three major taxa (plants, birds and butterflies), although this is one of the common ways to assess it [69,70]. Since ecological knowledge is multidimensional, it would be beneficial to assess it using a greater variety of approaches in the future.…”
Section: Limitationsmentioning
confidence: 99%
“…This has led some to argue that people's levels of direct experiences of nature may not have actually decreased [67,68]. Fourth, our study measured teachers' levels of ecological knowledge using only their ability to identify species of three major taxa (plants, birds and butterflies), although this is one of the common ways to assess it [69,70]. Since ecological knowledge is multidimensional, it would be beneficial to assess it using a greater variety of approaches in the future.…”
Section: Limitationsmentioning
confidence: 99%
“…Residence place: Many studies [67][68][69] demonstrated that individuals who live in urban areas document less CN compared with those who live in rural areas. In the present investigation, and despite the extent of green space in the sample area of residence (19,204 ha), no associations were identified between these two variables.…”
Section: Connectedness To Nature and Demographic Variablesmentioning
confidence: 99%
“…Concerns surrounding EoE-affecting all ages-continue to be shared in many countries (e.g. Bashan et al, 2021), although the prevalence of EoE as a global phenomenon has been questioned (Novotný et al, 2020;Oh et al, 2020). Furthermore, the value of using contact with, or knowledge of, nature as surrogates or prerequisites for 'nature connectedness' and pro-environmental behaviour continues to be much debated (Colléony et al, 2020;Passmore et al, 2021;Richardson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…using pictures, objects etc. as Bashan et al, 2021) or demonstrate specific kinds of knowledge about organisms, their status or ecology. The means of assessment will naturally follow from the way in which the specific domain is defined.…”
Section: Introductionmentioning
confidence: 99%